The International Journal of Museum Management and Curatorship (voortgezet als : Museum Management and Curatorship : The International Forum for Museum Professionals). (Guildford : Butterworth Scientific Ltd., 1982)
Museum Management and Curatorship (MMC) is an international peer-reviewed, journal aimed at museum professionals, consultants, educators, and researchers. Its content is intended to examine current issues in museum practice. The journal covers aspects such as administration, archives, collections management, communications, conservation, diversity, globalization, governance, interpretation, leadership, management, new technology, professional ethics, public service, purpose/mission, and social responsibility.(https://en.wikipedia.org/wiki/Museum_Management_and_Curatorship)
Online: https://www.tandfonline.com/toc/rmmc19/1/4
Engels
Tijdschriften
Keywords: museumbeleid